Menggali Potensi: Pengaruh Metode Pembelajaran Interaktif Moving Terhadap Motivasi Belajar Siswa - Fajira, Siti Regina Era; Ichwanto, Muhammad Aris; Sokhe, Akhmad (LPPM Institut Pendidikan Nusantara Global, 2024)
Education is the main pillar in the self-development of individuals and society. Education serves to transfer knowledge, skills and values from the younger generation. In this context, learning motivation is very important because it is an internal drive that encourages students to be able to actively participate in the learning process. However, during observations at one of the SMKs in Kediri Regency, it was shown that the learning motivation of students in class XI- DPIB (Building Modeling and Information Design) was still relatively low, with many students doing activities irrelevant to the lesson. The selection of appropriate learning methods is needed to be able to provide learning motivation for students.